Teacher Development for Equitable Mathematics Classrooms: Reflecting on Experience in the Context of Performativity - Sue Hough; Yvette Solomon (MDPI AG, 2023)
In this article, we chart the development of one of us-Sue Hough-from a teacher who wanted students to understand to one who gained new critical understandings of student thinking, pedagogy, and the very nature of mathematics. We comment on the role of research interventions and learning communities in this development, with a particular focus on Sue's encounter with Realistic Mathematics Education and the connections it makes between informal and formal mathematics through the pedagogy of guided reinvention. Development towards teaching that enables all learners to make sense of mathematics requires fundamental changes in pedagogic practice and a reconceptualisation of progress. Bringing about such radical change relies on one further aspect of Sue's story-the freedom to experiment and learn as a teacher. We note the remoteness of this possibility in a climate of performativity and marketised education, and we discuss the implications of Sue's journey for our pedagogical responsibilities in professional development today.